Renal Cell Carcinoma Mimicking Igg4-Related Pseudotumor in Autoimmune Pancreatitis - Khan, Muhammad Ali; Kamal, Sehrish; Ahmad, Usman; Chowdhury, Mohammed Andaleeb; Nawras, Ali (JOP. Journal of the Pancreas, 2014)
Context Autoimmune pancreatitis is classified into two distinct clinical profiles. Case report Type 1 autoimmune pancreatitis (AIP) is considered to be a manifestation of a novel clinicopathological entity called IgG4 related sclerosing disease, diagnosed using the Mayo Clinic HISORt criteria. Extra-pancreatic manifestations can include involvement of bile ducts, salivary gland, lung nodules, thyroiditis, tubulointerstitial nephritis, renal masses, and retroperitoneal fibrosis. Type 2 autoimmune pancreatitis on the other hand is confirmed by histologically seen duct centric pancreatitis without elevation of IgG4 or involvement of other organs. In type 1 autoimmune pancreatitis, extrapancreatic manifestations like bile duct strictures, tubulointerstitial nephritis, renal nodules, retroperitoneal fibrosis respond to steroid therapy. Conclusion We present a case of type 1 autoimmune pancreatitis in which the renal mass did not respond to steroid therapy and was later on found to be renal cell carcinoma. To the best of our knowledge this is only the third reported case of autoimmune pancreatitis in which the patient had renal cell carcinoma. Our case highlights the importance of close follow up of lesions that do not respond to steroid treatment which in this case proved to be renal cell cancer. Image: CT of the abdomen showing enlarged pancreas with loss of normal fatty lobulation.